ANALISIS IMPLEMENTASI MANAJEMEN SUPERVISI DI SMK MA’ARIF NU 2 AJIBARANG - Elsa Rakhmanita; Yuliono Yuliono; Lies Ning Ujiyanti; Iqlima Iqlima (Jurnal Manajemen Pendidikan, 2026)
Objective: This research is a qualitative research with a case study approach regarding the implementation of educational supervision at SMK Ma'arif NU 2 Ajibarang. This study aims to describe the implementation of educational supervision carried out in schools referring to the administrative supervision program and academic supervision. Educational supervision at SMK Ma'arif 0NU 2 Ajibarang is implemented through 5 stages, namely program planning, program socialization, administrative supervision, academic supervision, and evaluation and follow-up. Data collection was carried out using interview, observation, and documentation techniques. The data analysis technique used is the data analysis technique according to Miles and Huberman which consists of data collection, data reduction, data presentation, and drawing conclusions. The results of the study indicate that educational supervision at SMK Ma'arif NU 2 Ajibarang has been systematically programmed through the existence of educational supervision documents prepared by the Curriculum Division. Planning and socialization have been implemented optimally. However, the implementation of supervision, especially at the academic supervision stage, has not been optimally implemented because it was implemented in the second semester and not all teachers have carried out academic supervision. The school will conduct an evaluation of the entire program at the beginning of the school year as an effort to optimize the educational supervision program in the following school year.